Respuesta :

Step-by-step explanation:

To solve both questions you will have to use the Pythagoras theorem

[tex] {c}^{2} = {a}^{2} + {b}^{2} [/tex]

c being the hypotenuse

so to find AB we say

[tex] {ap}^{2} = {pb}^{2} + {ab}^{2} [/tex]

To make AB the subject of the formula, we take PB over. Therefore:

[tex] {ab}^{2} = {ap}^{2} - {pb}^{2} [/tex]

now we just substitute

[tex] {ab}^{2} = {13}^{2} - {5}^{2} [/tex]

[tex] {ab}^{2} = 169 - 25[/tex]

[tex] {ab}^{2} = 144[/tex]

square root both sides of the equation

[tex]ab = 12[/tex]

We then use the same formula to find AQ(which is a hypotenuse)

[tex] {aq}^{2} = {ab}^{2} + {bq}^{2} [/tex]

[tex] {aq}^{2} = {12}^{2} + {9}^{2} [/tex]

[tex] {aq}^{2} = 144 + 81[/tex]

[tex] {aq}^{2} = 225[/tex]

square root both sides

[tex]aq = 15[/tex]

ACCESS MORE